Measured ^1?Be and ?Be isotopes in manganese nodules and crusts from the Pacific and Atlantic oceans - P Sharma; Bammidipati L K Somayajulu (PANGAEA, 2023)
Ten large (surface area = 50-360 cm 2) manganese nodules and crusts from the Pacific, Atlantic and the Indian Oceanshave been selected for ^1?Be and ?Be isotopes evaluation. In-depth samples from each nodule were collected by chipping with the aid of a stainless steel chisel and hammer as well as using a dental drill. Powdered resulting material was ovendried (at 110°C overnight). Separation procedure used in either hydroxylamine hydrochloride or 6 M HCI + H2O2. 10Be concentration was evaluated using a radiometric beta counter. 9Be was measured using a HGA 500 graphite furnace (Perkin Elmer, U.S.A.) coupled to a model 305A atomic absorption spectrophotometer on a suitably diluted aliquot of acid leaches. The solution was dried at ll0°C, charred at 800°C and atomized at 2650°C using Ar as the carrier gas.